Changes in floodplain geo-ecology in the Belgian loess belt during the first millennium AD. (14th May 2021) - Broothaerts, Nils; Swinnen, Ward; Hoevers, Renske; Verstraeten, Gert
Abstract: Variation in human activities has greatly impacted the processes and intensities of erosion, sediment transport and storage throughout the Late Holocene, and many lowland rivers around the world have responded to these variations. Although this long-term process–response relationship has been established before, the effects of short-term ( c. 200-year) changes in human impact on lowland rivers are less well studied. Here, we followed an integrated approach whereby observations of floodplain changes are evaluated against detailed data on human impact for three lowland rivers in the Belgian loess belt: Dijle, Mombeek and Gete rivers. Pollen data were used to reconstruct changes in local and regional vegetation and to calculate human impact scores. Corings along transects and a database of c. 160 radiocarbon ages were used to reconstruct geomorphic changes in the river valleys. Our results show a decrease in human impact between 200 and 800 AD, which can be related to the decreased population density in Europe during the first millennium AD. During this period, forests in the studied catchments regenerated, soil erosion decreased, hillslope–floodplain connectivity decreased due to the regeneration of valley-side vegetation barriers, and sediment input in the floodplain decreased. A reaction to this decreased human impact can be observed in the river valleys during the first millennium AD, with a regrowth of the alder carr forest and an increase in the organic matter content of the alluvial deposits with a local reactivation of peat growth. The observed trajectories of Belgian river valleys during the first millennium AD provide more insight into the sensitivity of these river valleys to short-term variations in human impact. These results can in turn be used to better estimate the effects of future changes in the catchments on the fluvial system.